Answer:
x=a²+ab+b²/a+b , y=-ab/a+b
Explanation:
The system of the given equation may b written as:
ax+by-a²=0
bx+ay-b²=0
Here,
a1=a,b1=b,c1= -a²
a2=b,b2=a and c2= -b²
By cross multiplication we get
x/b*(-b²)-(-a²)*a = -y/a*(-b²)-(-a²)*b = 1/a*a-b*b
x/-b³+a³ = -y/-ab²+a²b = 1/a²-b²
Now
x/-b³+a³ = 1/a²-b²
x=a³-b³/a²-b²
x=(a-b)(a²+ab+b²)/(a-b)(a+b)
x=a²+ab+b²/a+b
And,
-y/-ab²+a²b = 1/a²-b²
-y=a²b -ab²/a²-b²
y=ab²-a²b/a²-b²
y=ab(b-a)/(a-b)(a+b)
y= -ab(a-b)/(a-b)(a+b)
y= -ab/a+b
Hence x=a²+ab+b²/a+b , y=-ab/a+b....